Exploring the impact of endogenous AHR ligand, 6-formylindole [3,2-b]carbazole (FICZ) on the microbiota-gut-brain axis in chronic stress-induced depression in rats - Najmeh Ekhtiyardar; Fereshteh Asadi Dolatabad; Amin Reza Akbarizadeh; Sanaz Salek; Neda Hajizadeh; Mohammad Javad Khoushnoud; Afshin Mohammadi-Bardbori (Shiraz University of Medical Sciences, 2024)
Aryl hydrocarbon receptor (AHR) is a nuclear receptor that mediates responses to environmental stimuli. The microbiome, influenced by factors such as nutrition, antibiotics, stress, and infection, plays a crucial role in mood, cognition, and mental health through the gut-brain axis. Chronic stress, known to impact both mental and physical health, is associated with depression onset, with social defeat being a potent stressor. This study investigates the effects of endogenous AHR ligands on the microbiota-gut-brain axis and behavioral changes in rats subjected to chronic stress. Male rats were divided into six groups: control, social defeat (SD), treatment with endogenous AHR ligand 6-formylindole [3,2-b]carbazole (FICZ) ± SD and treatment with tryptophan (TRP) ± SD. AHR ligands were administered weekly for one month, and fecal samples were collected for microbial analysis. Forced swimming and splash tests were used to assess depression behaviors. The results showed FICZ positively impacting depression-like behaviors, while chronic stress and depression correlated with decreased Lactobacillus species frequency, especially in the social defeat group. Further investigations are warranted to explore the impact of social defeat stress on microbial populations across other groups and other bacterial species.